Answer:
x = 3
y = 1
Step-by-step explanation:
(2x + 4y = 10) * 2 = (4x + 8y =20)
4x = 20 - 8y
Plug that into the other equation
(20 - 8y) - y = 11
-9y = -9
y = 1
Plug this value into one of the original equations
2x + 4(1) = 10
2x = 6
x = 3
Answer:
6x -16
Step-by-step explanation:
f(x) = 6x + 2
f(x-3) =
Replace x with x-3
f(x) = 6(x-3) + 2
Distribute
= 6x - 18 +2
= 6x -16
Answer:
70 miles
Step-by-step explanation:
30 minn+30 min=1 hour/60 min
30 min=35 miles
add the minutes together then add the miles together witch will give you
1 hour/60 min=70 miles
I’m pretty sure the correct answer is B